2019
DOI: 10.1002/cjs.11515
|View full text |Cite
|
Sign up to set email alerts
|

A directional look at F‐tests

Abstract: Directional testing of vector parameters, based on higher order approximations of likelihood theory, can ensure extremely accurate inference, even in high‐dimensional settings where standard first order likelihood results can perform poorly. Here we explore examples of directional inference where the calculations can be simplified, and prove that in several classical situations, the directional test reproduces exact results based on F‐tests. These findings give a new interpretation of some classical results an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…When the re-normalized saddlepoint approximation is exact, then the directional test will also be exact, as the re-normalization is automatically incorporated in (2.10). McCormack et al (2019) established this exactness for a number of tests for multivariate normal models, and Huang, Di Caterina, and Sartori (2022) were able to prove exactness for the case of testing a saturated Gaussian graphical model in Davison et al (2014, Sect. 5.3).…”
Section: Directional Tests In Linear Exponential Familiesmentioning
confidence: 85%
See 2 more Smart Citations
“…When the re-normalized saddlepoint approximation is exact, then the directional test will also be exact, as the re-normalization is automatically incorporated in (2.10). McCormack et al (2019) established this exactness for a number of tests for multivariate normal models, and Huang, Di Caterina, and Sartori (2022) were able to prove exactness for the case of testing a saturated Gaussian graphical model in Davison et al (2014, Sect. 5.3).…”
Section: Directional Tests In Linear Exponential Familiesmentioning
confidence: 85%
“…Still, in those settings the directional test proved to be uniformly more powerful than the likelihood ratio test and its modifications considered here. It is also noteworthy that for simpler testing problems in the multivariate normal model, McCormack et al (2019) showed that the directional test is equivalent to the uniformly most powerful invariant test based on the F statistic or Hotelling's T 2 statistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation